A Rare Association of Hydrops of Gall Bladder with Hepatitis E Infection - Sinha, R; Negi, V; Sawhney, MPS; Debnath, J (Journal of Nepal Paediatric Society, 2011)
Gall bladder distension with acute viral acalculous cholecystitis is an extremely rare event especially with Hepatitis E infection in paediatric cases with a high incidence of perforation, gallbladder necrosis and mortality. We report a four year old male child presenting with fever, vomiting, pain abdomen, mild hepatosplenomegaly and tenderness in right hypochondrium. Laboratory investigations revealed hyperbilirubinemia and elevated liver enzymes, but there was no evidence of bacterial or parasitic infection. Serology for viral hepatitis suggested acute Hepatitis E infection. Ultrasonographically distended inflamed gallbladder without calculous was observed. Finally acute acalculous cholecystitis due to Hepatitis E virus was diagnosed and the child responded to the conservative management. Key words: Acalculous cholecystitis; Hepatitis E; Pericholecystic fluid; Gallbladder thickening. DOI: http://dx.doi.org/10.3126/jnps.v31i3.5362 J Nep Paedtr Soc 2011;31(3): 216-222-223